The Role of Selected Pro-Inflammatory Cytokines in Pathogenesis of Ischemic Stroke - Pawluk, Hanna; Woźniak, Alina; Grześk, Grzegorz; Kołodziejska, Renata; Kozakiewicz, Mariusz; Kopkowska, Ewa; Grzechowiak, Elżbieta; Kozera, Grzegorz (Clinical interventions in aging, 2020)
Stroke is currently one of the most common causes of death and disability in the world, and its pathophysiology is a complex process, involving the oxidative stress and inflammatory reaction. Unfortunately, no biochemical factors useful in the diagnostics and treatment of stroke have been clearly established to date. Therefore, researchers are increasingly interested in the inflammatory response triggered by cerebral ischemia and its role in the development of cerebral infarction. This article gives an overview of the available literature data concerning the role of pro-inflammatory cytokines in acute stroke. Detailed analysis of their role in cerebral circulation disturbances can also suggest certain immune response regulatory mechanisms aimed to reduce damage to the nervous tissue in the course of stroke.